Catalyzing digital transformation through Smart Cities initiatives in Indonesian local government - Rio Yusri MAULANA; Usman MARJAMAT; Dimas SUBEKTI; Agung WICAKSONO (Smart Cities and Regional Development Journal)
In the domain of public service delivery, our research provides crucial guidance towards enhancing collaboration and achieving digital transformation. This study, focusing on Indonesian local government, uncovers insights that can reshape the smart governance dimension in the era of smart cities initiatives. Qualitative methods were used, conducting in-depth interviews with public officials, advanced observations, and detailed data collection from government agencies, NGOs, and citizens of Jambi, Indonesia. We identify significant challenges such as leadership commitment, digital talent resources, silos, and data integration deficiencies, emphasizing the need for sincere collaboration and advancing data interoperability. Addressing leadership awareness and the digital talent gap is essential for successful implementation, alongside improving cyber management and data security. Building on these challenges, the research highlights potential development areas including collaboration enhancement, prioritization of interoperability, robust data center development focusing on cyber management and data security, and targeted digital talent cultivation. Through research collaborations, this reseach aims to provide actionable insights and practical recommendations, contributing to effective governance. Tangible outcomes include a conceptual model, practical framework, and policy brief, empowering stakeholders. Ultimately, this research aspires to catalyze positive transformation, shaping a future of inclusive, innovative, and meaningful smart cities.